METAPHYSICAL POSTULATES OF EDUCATIONAL PRAXES: APPEAL TO THE FIRST PRINCIPLES OF METAPHYSICS AND THE PRINCIPLES OF BEING. - KAUKA, ELVIS OMONDI (IJRDO- Journal of Educational Research, 2017)
This study sought to investigate the metaphysical premises upon which educational praxessituate themselves. The study contends that education is a metaphysically laden activity. It usesanalytic and speculative methods to pinpoint areas of metaphysical concern with special intereston the learner and the learning process. The study proceeds by elucidating metaphysics inrelation to education, then analyses the first principles of metaphysics and how each one of theminform education praxis. In the second section the principles of being are discussed and appliedon education. These principles include Potency and act, essence and existence, and causality andparticipation. The conclusion drawn in this study, points to the fact that education revolvesaround a composite being(with form and matter) and so cannot be handled simplistically , anEssential being and so its universal value should not be eroded during education and existentialbeing with individuated experiences; pedagogical or otherwise.